Risk Management Plan: Expert Review of Applications for Marketing Authorisation in the EAEU Depending on the Type of Medicinal Product (Review) - T. M. Bukatina; E. V. Shubnikova (Безопасность и риск фармакотерапии, 2024)
INTRODUCTION. A risk management plan (RMP) is an important document for assessing and managing risks when using a medicinal product. An RMP is provided as part of the marketing authorisation application for a medicinal product. The requirements for the need to submit an RMP and the information in its sections depend on the type of medicinal product and marketing authorisation procedure. Marketing authorisation holders will benefit from an expert systematisation of the requirements for RMP submission outlined in the Eurasian Economic Union (EAEU) Rules for Marketing Authorisation and Expert Assessment of Medicinal Products for Human Use and Rules of Good Pharmacovigilance Practice (Eurasian Economic Commission Council Decisions Nos. 78 and 87 dated 03.11.2016, respectively), as this systematisation will contribute to a more accurate drafting of RMPs.AIM. This study aimed to analyse the requirements for submitting parts and modules of an RMP depending on the type of medicinal product being authorised according to the EAEU marketing authorisation procedures.RESULTS. This review analyses and systematises the requirements for the development of an RMP and the submission/non-submission of its main parts (I–VI) and Part II modules (CI–CVIII) depending on the type of medicinal product and marketing authorisation procedure. The article describes the principles for providing information in three main RMP sections: Safety Specifications (Part II), Pharmacovigilance Plan (Part III), and Risk Minimisation Measures (Part V). Flow charts illustrate summarised information on pharmacovigilance activities and risk minimisation measures that is included in an RMP. The article systematises the considerations for the analysis and evaluation of information for the main parts (I–VI) and Part II modules (CI–CVIII) of an RMP.CONCLUSIONS. The systematisation of the requirements of Eurasian Economic Commission Council Decisions Nos. 78 and 87 dated 03.11.2016, as well as the expert comments on considerations for RMP submission depending on the type of medicinal product and marketing authorisation procedure will help to improve the quality of RMPs and, in general, the safety of medicinal products authorised in the EAEU.